Isolamento da globulina majoritária, digestibilidade in vivo e in vitro das proteínas do tremoço-doce (Lupinus albus L.), var. Multolupa - Neves, Valdir Augusto [UNESP] (2006)
The aim of the present work was to isolate, purify and study some properties of the major globulin fraction from sweet lupin, var. Multolupa; as well as to evaluate the digestibility features of flour and isolated fractions. The protein fractions were separated by differential fractionation with different solvents. The lupin major globulin was isolated, purified by Q-Sepharose chromatography when it showed only one protein peak. The major protein presented a molecular weight of 162.5 ± 10.0 kDa, determined on Sephacryl S-300 chromatography; and subunits between 20 to 70 kDa on SDS-PAGE. The protein solubility in relation to pH and NaCl concentrations showed a typical S-like curve for globulins. The flour and the isolated protein fractions, albumins, globulins and glutelins were evaluated by in vitro and in vivo experiments. The in vitro and in vivo digestibility assays revealed a high digestibility for the globulin, followed by glutelin, albumin and the flour. The globulin in vivo digestibility did not differ significantly from that obtained to casein. Despite the high digestibility encountered for the major protein fraction and protein fractions, the use as the only protein source in the diets revealed low values for RNPR (relative net protein ratio), showing it to be insufficient in terms of sustaining the growth of animals, comparatively to casein.